ANTIBIOGRAM ASSAY OF E.COLI ISOLATES IN PATIENTS WITH URINARY TRACT INFECTION - AHMAD , S; KHAN, H; HANAN, F; KHAN, SU; FAISAL, MS; ULHAQ, I; SHAH, M; ALI, L (Biological and Clinical Sciences Research Journal, 2024)
Screening of prevalent bacterial pathogens for antibiotic susceptibility profiles in different regions is necessary. E. coli and other pathogens are so common in our environment that it is essential to monitor trends in antibiotic susceptibility regularly. Objective: The aim of the study was to find out the antibiotic susceptibility pattern of E.coli isolates in patients with urinary tract infection. Methods: This study was conducted at the Saidu Group of Teaching Hospital Swat after taking permission from the ethical committee of the institute. We collected a total of 900 urine samples from males and females of all ages for culture and sensitivity. The Kirby-Bauer disc diffusion method was used to assess the antibiogram on Mueller-Hinton agar. The plates were kept in incubator at 37°C for the 48 hours, and the inhibition zone was measured. The antibiogram was performed by Kirby-Bauer disc diffusion method applying various antibiotics. The bacterial strains were classified in to three majors groups on the basis of antibiotic susceptibility pattern resistant (R) sensitive (S), and intermediate (I). Data was statistically analyzed presented in the tables and figures. Results: For culture and sensitivity testing, a total of 900 urine samples from patients with suspected UTIs were obtained from the several departments’ inpatient and outpatient to the microbiological lab. Substantial bacteriuria was noted in 250 (27.7%). The most prevalent bacteria isolated was E.coli (55%) and its antibiogram was carried out. Ampicillin had the highest proportion of resistance (96.1%), followed by Ceftriaxone (91%), Moxifloxacin (87.1%), and Ceftazidime (75.5%). Whereas it was sensitive to Fosfomycin (94.2%), followed by Sulzone ( 84.3%), Imepinem (84.3%) and Amikacin (78%). Conclusion: It was concluded from the current study that the most prevalent bacteria causing urinary tract infection was E.coli, and this bacteria showed remarkable resistance against Ampicillin Ceftriaxone, Moxifloxacin, and Ceftazidime. The most used bacterium antibiotics for therapy were Fosfomycin, Imepinem and Amikacin. Therefore, antibiotic susceptibility should be considered before therapy.